Prevalence and association analysis of obstructive sleep apnea with gender and age differences – Results of SHIP‐Trend. (1st October 2018) - Fietze, Ingo; Laharnar, Naima; Obst, Anne; Ewert, Ralf; Felix, Stephan B.; Garcia, Carmen; Gläser, Sven; Glos, Martin; Schmidt, Carsten Oliver; Stubbe, Beate; Völzke, Henry; Zimmermann, Sandra; et al.
Abstract: Identification of obstructive sleep apnea and risk factors is important for reduction in symptoms and cardiovascular risk, and for improvement of quality of life. The population‐based Study of Health in Pomerania investigated risk factors and clinical diseases in a general population of northeast Germany. Additional polysomnography was applied to measure sleep and respiration with the objective of assessing prevalence and risk factors of obstructive sleep apnea in a German cohort. One‐thousand, two‐hundred and eight people between 20 and 81 years old (54% men, median age 54 years) underwent overnight polysomnography. The estimated obstructive sleep apnea prevalence was 46% (59% men, 33% women) for an apnea–hypopnea index ≥5%, and 21% (30% men, 13% women) for an apnea–hypopnea index ≥ 15. The estimated obstructive sleep apnea syndrome prevalence (apnea–hypopnea index ≥5; Epworth Sleepiness Scale >10) was 6%. The prevalence of obstructive sleep apnea continuously increased with age for men and women with, however, later onset for women. Gender, age, body mass index, waist‐to‐hip ratio, snoring, alcohol consumption (for women only) and self‐reported cardiovascular diseases were significantly positively associated with obstructive sleep apnea, whereas daytime sleepiness was not. Diabetes, hypertension and metabolic syndrome were positively associated with severe obstructive sleep apnea. The associations became non‐significant after adjustment for body mass. Women exhibited stronger associations than men. The prevalence of obstructive sleep apnea was high, with almost half the population presenting some kind of obstructive sleep apnea. The continuous increase of obstructive sleep apnea with age challenges the current theory that mortality due to obstructive sleep apnea and cardiovascular co‐morbidities affect obstructive sleep apnea prevalence at an advanced age. Also, gender differences regarding obstructive sleep apnea and associations are significant for recognizing obstructive sleep apnea mechanisms and therapy responsiveness.